Kdm6b and Pmepa1 as Targets of Bioelectrically and Behaviorally Induced Activin A Signaling - Link, Andrea; Kurinna, Svitlana; Havlicek, Steven; Lehnert, Sandra; Reichel, Martin; Kornhuber, Johannes; Winner, Beate; Huth, Tobias; Zheng, Fang; Werner, Sabine; Alzheimer, Christian (Molecular Neurobiology, 2016)
The transforming growth factor-? (TGF-?) family member activin A exerts multiple neurotrophic and protective effects in the brain. Activin also modulates cognitive functions and affective behavior and is a presumed target of antidepressant therapy. Despite its important role in the injured and intact brain, the mechanisms underlying activin effects in the CNS are still largely unknown. Our goal was to identify the first target genes of activin signaling in the hippocampus in vivo. Electroconvulsive seizures, a rodent model of electroconvulsive therapy in humans, were applied to C57BL/6J mice to elicit a strong increase in activin A signaling. Chromatin immunoprecipitation experiments with hippocampal lysates subsequently revealed that binding of SMAD2/3, the intracellular effectors of activin signaling, was significantly enriched at the Pmepa1 gene, which encodes a negative feedback regulator of TGF-? signaling in cancer cells, and at the Kdm6b gene, which encodes an epigenetic regulator promoting transcriptional plasticity. Underlining the significance of these findings, activin treatment also induced PMEPA1 and KDM6B expression in human forebrain neurons generated from embryonic stem cells suggesting interspecies conservation of activin effects in mammalian neurons. Importantly, physiological stimuli such as provided by environmental enrichment proved already sufficient to engender a rapid and significant induction of activin signaling concomitant with an upregulation of Pmepa1 and Kdm6b expression. Taken together, our study identified the first target genes of activin signaling in the brain. With the induction of Kdm6b expression, activin is likely to gain impact on a presumed epigenetic regulator of activity-dependent neuronal plasticity.
EVALuna2:2488